Growth of LiNi0.5Mn1.5O4 crystals on reduced graphene oxide sheets for high energy and power density charge storage - Gajraj, V.; Rajan, Jose; Mariappan, Chinnasamy Ramaraj (Elsevier, 2020)
Spinel-type lithium manganates are actively considered to develop cost-effective energy/charge storage devices. In this article, we show the growth of LiNi0.5Mn1.5O4 nanocrystals on reduced graphene oxide (rGO) sheets, which offer impressive improvements in their charge storage capability than that can be achieved using bare LiNi0.5Mn1.5O4 nanocrystals. X-ray diffraction, Raman spectroscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and electron microscopy techniques are employed to demonstrate the embedment of LiNi0.5Mn1.5O4 particles on rGO sheets. As a single electrode, LiNi0.5Mn1.5O4-rGO composite electrode deliver ∼3-fold enhanced charge storability (∼572 F g−1 /∼175 mA h g-1 at 3.75 A g-1) in 5 M LiNO3 electrolyte than the bare LiNi0.5Mn1.5O4 electrode. The electrochemical charge storage processes are investigated via the Dunn’s approach. The major charge storage mechanism of the samples is diffusion controlled at slow scan rate. A practical hybrid battery – supercapacitor device is fabricated in the LiNi0.5Mn1.5O4-rGO//activated carbon configuration, which deliver energy density in the 60 – 23 Wh kg-1 range at a power density in the 1.2−13 kW kg-1 range with an output voltage of 0–2.0 V, excellent cycling stability, and rate capability.